ANALISIS PERTIMBANGAN HAKIM DALAM MENERAPKAN SANKSI PIDANA TERHADAP ANAK YANG BERKONFLIK DENGAN HUKUM (STUDI KASUS: PUTUSAN NOMOR 9/PID.SUS ANAK/2017/PN PWD) - Lisa Andriana (2022)
The issue of punishment of children in conflict with the law is regulated in Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. But in reality, there are still criminal decisions from the Court according to the author that are not in accordance with these rules. One example is the case that occurred in the Purwodadi District Court Decision Number 9/Pid.Sus Anak/2017/Pn Pwd. The purpose of this study was to find out what the judges' considerations were in applying criminal sanctions in the Purwodadi District Court Decision Number 9/Pid.Sus Anak/2017/Pn Pwd along with the suitability of the Purwodadi District Court Decision Number 9/Pid.Sus Anak/2017/Pn Pwd with the provisions of Article 81 of Law Number 11 of 2012. In this writing the author uses a normative juridical research method due to legal problems, there is a discrepancy between the Purwodadi District Court Decision Number 9/Pid.Sus Anak/2017/Pn Pwd with other statutory provisions . The nature of this writing is descriptive analytical, which is a method that takes written data to be described in order to obtain a comprehensive picture and understanding. The results of this study are that the punishment for children who are in conflict with the law is that there is a basic punishment for children consisting of a warning sentence, a criminal conditional punishment, job training, coaching in the institution, and the last one is imprisonment. Regarding imprisonment, it is clarified in Article 81 Paragraph (5) of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System which states that imprisonment for children is only used as a last resort. Meanwhile, the Purwodadi District Court Decision Number 9/Pid.Sus Anak/2017/Pn Pwd does not apply this regulation, so it can be concluded that there is a legal conflict between the Purwodadi District Court Decision Number 9/Pid.Sus Anak/2017/Pn Pwd and the Act. Law Number 11 of 2012. Then the author compares the problem with other examples of decisions including the Cibinong District Court Decision Number 12/Pid.Sus-Anak/2020/Pn.Cbi. and the Denpasar District Court where in its decision Number: 25/Pid.Sus-Anak/2019/PN.Dps.